Plate-Rod Osteosynthesis in Dogs and Cats - de Souza, Mariana de Jesus; Ferreira, Marcio Poletto; Amadori, Augusto; Kretzer, Rafael Carneiro; Junqueira, Amanda; Hergemoller, Francine; Amorim Sebastião, Grasiele (Acta Scientiae Veterinariae, 2019)
Background: Most fractures are caused by traumatic processes due to car accidents, but they can also occur due to bullets, fights and falls. Surgical stabilization is often necessary and shows high rates of bone healing when its basic concepts are followed. The objective of this study is to report cases of shaft fracture in long bones stabilized with intramedullary pin and plate (IMPP) in order to evaluate pre- and postoperative clinical and radiographic signs, correlating the ideal surgical technique described on recent studies with complications resulting from the surgical procedure. Cases: This study includes patients undergoing osteosynthesis with intramedullary pin and plate from January 2015 to December 2016 at the Veterinary Medical Teaching Hospital of UFRGS. During this period, 13 animals (five cats and eight dogs) with long bone fractures were treated with the abovementioned association. Information on breed, age, sex, etiology of the fracture, affected bone, clinical signs, osteosynthesis technique, clinical progress, fracture healing, and postoperative complications was collected for the study. Late postoperative recovery was evaluated by telephone contact with owners. The mean age was 5.4 years (3 months - 15 years) and body weight 17.66 kg (3 - 28.4 kg). The fractures were due to being hit by a vehicle (5), bites (1), accident with a toy (1), and unknown (6). Discussion: All cases included in this study were in the femur, humerus or tibia. Fractures in the radius are also frequent in small animal traumatology, but in this case the use of an intramedullary pin is not recommended. All animals had diaphyseal fractures, which is an important prerequisite for IMPP stabilization. The IMPP association is mainly indicated in cases of comminuted fractures, when it is anatomically impossible to reduce fracture fragments, as occurred with nine patients in this study. The plate did not break of fail in any of the cases, as the association of an intramedullary pin with the plate significantly reduces tension on the plate, increasing bending strength up to ten times. One of the animals presented severe postoperative pain and could not adequately lean on the operated limb. Orthopedic and neurological evaluation led to the conclusion that the long pin in the region of the subtrochanteric fossa could be injuring the sciatic nerve and the animal was reoperated to cut the pin shorter. Pain stopped and after seven months the animal could lean on the limb and move normally, being proprioceptive and showing no pain on palpation and manipulation. The pin used in the IMPP technique should fill 30 to 40% of the diameter of the intramedullary canal at its narrowest portion. Of the 13 patients included in this study, six received pins within the recommended diameter, one received a pin larger than recommended, and five received pins smaller than recommended. The mean diameter of the pin related to the diameter of the medullary canal was 32.3% (19% - 54.8%). The bone healing rate described for IMPP is high (98%), three patients returned for this study reevaluation and all of them presented visible radiographic bone healing. We concluded that osteosynthesis associated with the use of intramedullary pin and plate resulted in adequate stabilization of fractures in the femur, tibia and humerus, allowing fast functional recovery with low complication rates.